Dissolved methane concentrations and oxidation rates around South Georgia, in summer 2022 - Bussmann, Ingeborg; Gentz, Torben; Kasten, Sabine (PANGAEA, 2025)
On the cruise PS133/2 water samples were taken from the rosette and filled without bubbles into 120 ml glass bottles. Samples were taken from surface water and several depths down to the bottom. Water samples were analysed for dissolved methane concentration, methane oxidation rate and the diffusive flux was calculated. CH4 concentrations were determined on board in duplicate by gas chromatography with the head space method (Magen et al. 2014). Methane oxidation rates were determined on board in triplicate with tritium labelled methane according to Bussmann et al 2015. To calculate the diffusive methane flux between sea water and atmosphere based on the equation of Ho et al al 2006, we used the water temperature and salinity from the ship's CTD for the methane solubility (Wiesenburg, Guinasso, 1979); wind speed from the ship's weather station which was corrected for 10 m height, and the atmospheric CH4 concentration was taken from https://doi.pangaea.de/10.1594/PANGAEA.983729 .
Keywords: dissolved methane concentration; methane oxidation rate; PS133/2